A BRIEF REVIEW ON PHYTOCHEMICAL AND PHARMACOLOGICAL PROFILE OF CARISSA SPINARUM L. - Ansari, Imtiyaz; Patil, Diptesh T (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Carissa spinarum L. belongs the Apocynaceae family, which officially itself has 94 synonyms and misspelled, misapplied, invalid, and illegitimate names. The plant is known as Magic Shrubâ€ in some of the African countries, as it is a source of treatment for various diseases and disorders. The plant contains certain major bioactive constituents such as acids, glycosides, terpenoids, alkaloids, tannins, and saponins which are responsible for medicinal value. Traditionally, the plant is used for treatment of malaria, chest complaints, stomach-ache, diarrhea, worms, a cough remedy, eye cataracts, gastric ulcers, polio, cancer, hypertension, kidney complication and for treating herpes, infertility, diabetes, asthma, rheumatism, and infections such as gonorrhea, syphilis, sickle-cell anemia, hernia, rabies, typhoid fever, jaundice, sexual asthenia in males, measles, and as a cough expectorant. Apart from this, the plant is evaluated for various pharmacological activities by employing the animal models. The review has been written with the aim to provide a direction for further clinical research to promote safe and effective herbal treatments to cure a number of diseases.